"These depressed times": architectural and decorative strategies in Christchurch in the financially stringent years of the early 1890s - Halliday, Jessica (Architectural History Aotearoa, 2007)
In 1893 The Press commended Charles Clark for his "energy and faith in the future of Christchurch" in commissioning Collins & Harman to design a new building in Cathedral Square in Christchurch "in these depressed times." The first half of the 1890s saw the continuation of the long depression that had marked New Zealand the previous decade. In contrast to the abounding intensity that can be inferred from the broad descriptions of New Zealand architecture at the end of the nineteenth century, architectural endeavours at this time were often constrained by limited opportunities and restricted budgets. This paper considers Christchurch architecture of the early 1890s in the context of these financially stringent years, examining most closely the practice of Armson, Collins & Harman.